The Complex Association Between Fear of Falling and Mobility Limitation in Relation to Late-Life Falls: A SHARE-Based Analysis. (July 2018) - Litwin, Howard; Erlich, Bracha; Dunsky, Ayelet
Objective: This study examines fear of falling (FOF) in relation to falls in light of mobility limitation.Method: Data on community-dwelling older Europeans, aged 65+, were drawn from two consecutive waves of the Survey of Health, Ageing and Retirement in Europe (SHARE). The analysis regressed fall status in 2013 on reported FOF 2 to 3 years earlier, controlling for previous falls.Results: FOF predicted subsequent falls when mobility limitation was low to moderate. However, the effect of FOF on fall probability was reversed when mobility limitation was high.Discussion: The analysis underscores a complex association between FOF and mobility limitation in relation to late-life falls. People who are worried about falling tend to fall more. Those having high mobility limitation but lacking FOF are also more likely to fall. In cases of considerable mobility limitation, FOF may act as a protective buffer. The less worried in this group, however, may be subject to greater falling, and thus require greater attention.